Analysis of the effects of electrostatic interactions on protein transport through zwitterionic ultrafiltration membranes using protein charge ladders. Issue 21 (8th October 2014) - Hadidi, Mahsa; Zydney, Andrew L.; Escobar, Isabel C.; Van der Bruggen, Bart
ABSTRACT A large number of studies have shown that zwitterionic ultrafiltration membranes have very low protein fouling due to the strongly hydrated structure of the zwitterionic modification. However, there is much less known about the effects of the zwitterionic functionality on the electrostatic interactions governing protein transport through these membranes. The objective of this work was to use protein charge ladders to evaluate the effects of electrostatic interactions on protein transport through cellulosic ultrafiltration membranes modified with a zwitterionic functionality. Data were obtained using protein charge ladders formed by reacting lysozyme and α‐lactalbumin with acetic anhydride to generate a series of protein derivatives (ladders) differing by single charge groups but with essentially identical size. Protein retention was greater for the more positively charged elements within the charge ladder, consistent with a weak electrostatic repulsion from the zwitterionic membrane which had a small positive charge at pH 7. Data for all elements of the protein charge ladder (both positively and negatively charged) were in excellent agreement with calculations of a theoretical model based on the partitioning of a charged sphere (protein) in a charged cylinder. The results demonstrate the potential of using zwitterionic membranes for enhanced ultrafiltration with high selectivity and minimal fouling. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41540.